Researcher-implementer partnerships in nutrition-sensitive agriculture programming: Lessons from IFPRI’s work with Helen Keller International and the World Food Programme - Sproule, Kathryn; Bliznashka, Lilia (International Food Policy Research Institute, 2021)
Researcher–implementer partnerships are frequently mentioned as key components of agricultural research for development (AR4D) programs. However, there is little information about what these types of partnerships look like, how they perform, and what factors facilitate and/or constrain their performance. By documenting and analyzing two partnerships in detail, including their history, formation, outputs, and outcomes, this study seeks to raise awareness about and improve understanding of long-term researcher–implementer partnerships. The lessons learned from these partnerships can be used by both the International Food Research Institute (IFPRI) and its implementing partner organizations, as well as other research and implementing organizations interested in engaging in or supporting such partnerships for AR4D in the future. The study was carried out through four case studies. Case 1 focused on a long-term partnership between IFPRI and Helen Keller International (HKI), documenting how it was formed, how it operated, and what outputs it produced. Case 2 looked at the evidence generated by this partnership on the effectiveness of homestead food production (HFP) programs on nutrition-related outcomes and its use by funders, implementers, and researchers. Case 3 looked at how and to what extent the approaches developed by the partnership for the design, implementation, and evaluation of programs — specifically the program impact pathway (PIP) approach — have influenced the broader field of program evaluation. Case 4 examined a partnership between IFPRI and the World Food Programme (WFP), documenting how it was formed, how it operated, and what outputs it has produced to date. The four case studies were completed through a series of in-depth interviews (IDIs) with key informants from a number of research, implementer, and funder organizations. Data from the IDIs were complemented by document and literature reviews.